The jewel of seven stars - Stoker, Bram 1847-1912 (Oxford popular fiction, 1996)
In the early hours of the morning a young lawyer is called to the home of a beautiful woman he has just met, where her archaeologist father lies in a coma, the victim of a mysterious attack. The injured man is discovered to be dabbling in ritual magic in an attempt to raise an ancient Egyptian queen from the dead. As the hour of his great experiment approaches, a deadly supernatural struggle begins. First published in 1903 as a successor to Dracula, this original version of the novel has never been reprinted before. This edition also includes the alternative ending for the 1912 revised edition.